Hubungan Tingkat Pengetahuan Dengan Kejadian Ulkus Diabetik Pada Pasien Diabetes Mellitus - Sri Enawati; Dessy Marendra Rizki Permana; Yuli Widyastuti; Sri Handayani; Muhammad Anis Sumaji (Journal Pharma Saintika, 2020)
Background: Diabetes Mellitus is a chronic metabolic disorder caused by the pancreas not being able to produce enough insulin or the body cannot use the insulin that has been produced effectively. In 2019 the State of Indonesia was ranked 7th among 10 countries with the number of people with Diabetes Mellitus, which was 10.7 million, Meanwhile, according to the Surakarta City Health Office, people with Diabetes Mellitus in 2019 were 17,077 cases. Patients with Diabetes Mellitus are at risk of developing diabetic ulcers. The worldwide prevalence of complications in the form of diabetic ulcers is 9.1 – 26.1 million people. Objective: To determine the relationship between the patient's level of knowledge about diabetic ulcers and the incidence of diabetic ulcers in Diabetes Mellitus patients at the Surakarta City Hospital. Research Methods: This research is quantitative research with a correlation method. Research design with the cross-sectional approach. This research was conducted at the Surakarta City Hospital from January 11 – to February 11, 2022, with a purposive sampling technique and the number of respondents was 20. Using Fisher’s Exact statistical test analysis. Results: it was found that the probability (p) of the significance test of the two variables was 0.000, so the p-value was 0.000 <0.005, so it can be concluded that there is a relationship between the level of knowledge and the incidence of ulcers in Diabetes Mellitus patients, with a positive correlation coefficient. Conclusion: There is a positive and significant relationship between the level of knowledge and the incidence of diabetic ulcers in patients with diabetes mellitus with a p-value of 0.000 <0.005